Sustainability of a beach resort: a case study - Mustapha, Mazlina; Awang, Khairil Wahidin (Science Publishing Corporation, 2018)
In Malaysian Eleventh Plan 2016-2020, tourism is one of the service sectors given priority by the government. It is claimed that the increase in tourist arrivals help to support the deficit reduction in service sector by contributing to the growth of the nation. Furthermore, the quick growth of tourism in Southeast Asia, as a result of amongst others attractive sandy beaches and nature, beach resorts have been on the receiving end of attention and focus by the tourists. However, prior studies claimed that these resorts were not properly managed and further actions need to be taken to ensure its sustainability. Thus, this case study aims to examine performance management of a beach resort in ensuring its sustainability. Specifically, this study explores the cost saving strategies adopted by this resort through its 25 years of operation. This resort is located on an island in Terengganu. The resort owner and employees were interviewed. The interview results appear to indicate that various strategies were implemented by the resort to manage their performance and ensure its sustainability in the business. Family members hold important positions in the resort to ensure the smooth running of the operation. Cost saving activities and smart business arrangements were made with suppliers to reduce its outflows.